Effect of histone modifications on alternative splicing in gastric cancer - Jin-Xuan Zhao; Xiao-Wei Li; Bing-Yu Shi; Fang Wang; Zheng-Rong Xu; Hai-Lan Meng; Yun-Yan Su; Jing-Mei Wang; Nong Xiao; Qiong He; Ya-Ping Wang; Yi-Mei Fan (Tumor Biology)
hMLH1 is one of the mismatch genes closely related to the occurrence of gastric cancer. Epigenetic regulation may play more important roles than gene mutations in DNA damage repair genes to drive carcinogenesis. In this article, we discuss the role of epigenetic changes, especially histone modifications in the regulation of hMLH1 alternative splicing. Our results showed that hMLH1 del Ex10, del Ex11, del Ex10–11, del Ex16 and del Ex17 transcripts were ubiquitous in sporadic Chinese gastric cancer patients and gastric cancer cell lines. Lower level of H4K16ac and H3ac was detected in hMLH1 exon 10–11 region in gastric cancer cell lines when compared with human gastric mucosal epithelial cell line GES-1. A significant decrease of hMLH1 del Ex11 and del Ex10–11 was observed in gastric cancer cell lines after trichostatin A treatment. H3K36me3 and H3K4me2 levels were lower in hMLH1 exon 10–11 and exon 16–17 regions in gastric cancer lines when compared with GES-1. Aberrant transcripts such as hMLH1 del Ex11 and del Ex10–11 were significantly higher in gastric cancer cell lines after small interfering RNA–mediated knockdown of SETD2 (the specific methyltransferase of H3K36). The hMLH1 del Ex10 and del Ex10–11 transcripts were increased after interference of SRSF2. Taken together, our study demonstrates that lower level of histone acetylation and specific histone methylation such as H3K36me3 correlate with aberrant transcripts in hMLH1 exon 10–11 region. SRSF2 may be involved in these specific exons skipping as well.